2013
DOI: 10.1111/j.1464-410x.2012.11754.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette‐Guérin immunotherapy for genitourinary cancer

Abstract: What's known on the subject? and What does the study add? The administration of Bacillus Calmette‐Guérin (BCG) immunotherapy has become the standard of care for high‐grade non‐muscle invasive bladder cancer (NMIBC) and carcinoma in‐situ (CIS) in terms of prevention of recurrence and progression. While most agree on a 6 week induction cycle, various maintenance schedules (if any at all) have been implemented without a unifying consensus. This review assesses the historical emergence of BCG immunotherapy, begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 60 publications
1
100
0
2
Order By: Relevance
“…6 Even though new treatments have been reported, more results and larger studies are needed. 6,12,[14][15][16] Colombo and colleagues found that C-HT is more effective than MMC alone. 17 The 10-year disease-free survival rate for C-HT and MMC alone were 53% and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…6 Even though new treatments have been reported, more results and larger studies are needed. 6,12,[14][15][16] Colombo and colleagues found that C-HT is more effective than MMC alone. 17 The 10-year disease-free survival rate for C-HT and MMC alone were 53% and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used treatment, repeated 6week instillations, has been found to be ineffective in one RCT. 13 Five RCTs com pared non3week maintenance schedules to BCG induction only (Table 1). [14][15][16][17][18] None of these alternative maintenance schedules showed a statistically significant reduction in recurrence (range -4% to 22%, average 7%).…”
Section: Optimal Schedule and Duration Of Therapymentioning
confidence: 99%
“…However, other idea is that the profound effect of BCG on stimulation of the immune system is well recognized 6,7 . Evidence to date supports the idea that the antitumor effects of BCG are produced by an interplay between the direct effects on tumor cells by BCG infection and the host's immune response 8 .…”
Section: Mechanism Of Action Of Bcgmentioning
confidence: 99%